The Effects of Eggshell Ash on Strength Properties of Cement-stabilized Lateritic - U. N, Okonkwo; I. C, Odiong; E. E, Akpabio (International Journal of Sustainable Construction Engineering and Technology, 2012)
Eggshell ash obtained by incinerating Fowls’ eggshells to ash has been established to be a good accelerator for cement-bound materials and this would be useful for road construction work at the peak of rainy seasons for reducing setting time of stabilized road pavements. However this should be achieved not at the expense of other vital properties of the stabilized matrix. This is part of the effort in adding value to agricultural materials which probably cause disposal problems. Thus this study aimed at determining the effect of eggshell ash on the strength properties of cement-stabilized lateritic soil. The lateritic soil was classified to be A-6(2) in AASHTO rating system and reddish-brown clayey sand (SC) in the Unified Classification System. Constant cement contents of 6% and 8% were added to the lateritic soil with variations in eggshell ash content of 0% to 10% at 2% intervals. All proportions of cement and eggshell ash contents were measured in percentages by weight of the dry soil. The Compaction test, California Bearing Ratio test, Unconfined Compressive Strength test and Durability test were carried out on the soil-cement eggshell ash mixtures. The increase in eggshell ash content increased the Optimum Moisture Content but reduced the Maximum Dry Density of the soil-cement eggshell ash mixtures. Also the increase in eggshell ash content considerably increased the strength properties of the soil-cement eggshell ash mixtures up to 35% in the average but fell short of the strength requirements except the durability requirement was satisfied.